Long-term outcome of full tendon vertical rectus transposition with Foster suture in unilateral complete sixth cranial nerve palsy - Honglertnapakul W (Dove Medical Press, 2019)
Worawalun Honglertnapakul,1,2 Sirinuch Sawanwattanakul,1,2 Parnchat Pukrushpan,1,2 Pokpong Praneeprachachon,1–3 Supharat Jariyakosol1,2 1Department of Ophthalmology, Faculty of Medicine, Chulalongkorn University, Bangkok, Thailand; 2Ophthalmology Department, King Chulalongkorn Memorial Hospital, the Thai Red Cross Society, Bangkok, Thailand; 3Rutnin Eye Hospital, Bangkok, Thailand Purpose: To evaluate the success rate and long-term motor and sensory outcomes of the full tendon vertical rectus transposition (VRT) with Foster suture for unilateral complete sixth cranial nerve palsy. Patients and methods: We reviewed the medical records of patients with unilateral acquired sixth cranial nerve palsy who underwent unilateral full tendon VRT with Foster suture between 2005 and 2016 and had a follow-up of ≥2 years. Data on pre- and postoperative diplopia, face turn, ocular deviation, and limitation of abduction were collected. A successful outcome was defined as a horizontal deviation ≤10 prism diopter (PD) of ortho in a primary position at distance and absence of diplopia. Results: A total of 20 patients were included in this study. Median (IQR) preoperative deviation was esotropia 65 (40–130) PD, which improved to 10 (-4 to 45) PD postoperatively. Median (IQR) improvement of esotropia was 54 (30–76) PD (P<0.001). Median (IQR) preoperative limitation of abduction was -15° (-22.5° to 10°; negative value means before reaching midline), which improved to 15° (7.5°–45°) pass midline postoperatively. Median (IQR) improvement of abduction deficit was 26° (15°–35°) (P<0.001). Successful surgical outcomes were obtained in eleven patients (55%). All patients in the non-successful group (n=9, 45%) had residual esotropia. Two of them underwent additional bilateral medial rectus recession. No postoperative vertical deviation or torsional diplopia was observed. Conclusion: In our series, the full tendon VRT with Foster suture in unilateral complete sixth cranial nerve palsy resulted in significant improvement of the ocular alignment and range of abduction over the 2-year follow-up period. Keywords: sixth cranial nerve palsy, full tendon vertical rectus transposition, Foster suture, posterior fixation suture, lateral fixation suture